Respuesta :

Answer:

12

Step-by-step explanation:

Using formula

distance = [tex]\sqrt{ (y2 - y1)^{2} + (x2- x1)^2}[/tex]

Then input the values:

Distance = [tex]\sqrt{ (0 - 0)^{2} + (-8- 4)^2}[/tex]

               = [tex]\sqrt{0 + 144}[/tex]

               = 12

Given are two values.

Let :-

[tex]4 = {x}^{1} [/tex]

[tex]0 = {y}^{1} [/tex]

[tex] - 8 = {x}^{2} [/tex]

[tex]0 = {y}^{2} [/tex]

By distance formula,

[tex] \sqrt{ ({x}^{2} - {x}^{1})^{2} + ( {y}^{2} - {y}^{1})^{2} }[/tex]

[tex] \sqrt{ (- 8 - 4)^{2} + (0 - 0) ^{2} } [/tex]

[tex] \sqrt{( - 12)^{2} + 0^{2} } [/tex]

[tex] \sqrt{144 + 0} [/tex]

[tex] 12[/tex]

Therefore, the distance is 12